European Central Bank monetary policy´s effects on inequality - Chacón Piñero, Lorena (Papeles de Europa, 2019)
Monetary policy can modify the individual well-being and the inequality in a heterogeneous way, even if it reaches its main objectives, such as price stability. Since inequality is a problem that is growing internationally, this article studies how and through which channels monetary policy can influence on inequality. In this way, effects can be produced through variations in interest rates and income growth, among other variables that are included in the transmission mechanism of monetary policy.
Keywords: Inequality; interest rates; monetary policy